Schematism and Free Play: The Imagination’s Formal Power as a Unifying Feature in Kant’s Doctrine of the Faculties - Hoerth, Jackson (Con-Textos Kantianos. International Journal of Philosophy, 2020)
The role of the imagination within Kant’s Critical framework remains an issue for any attempt to unify the three Critiques through the Doctrine of the Faculties. This work provides a reading of the imagination that serves to unify the imagination through its formal capacity, or ability to recognize harmony and produce the necessary lawfulness that grounds the possibility of judgment. The argument of this work exists in 2 parts. 1) The imagination’s formal ability is present, yet concealed, as early as the Schematism in the Critique of Pure Reason and reaches its fullest exposition in instances of harmonious free play in the Critique of the Power of Judgment. 2) This formal capacity is key to not only demonstrating the imagination as an original, unified, and independent faculty across Kant’s Critical framework, but also serves as grounds for the purposiveness of nature – a key aspect of Kantian aesthetics.
Keywords: Imagination; Purposiveness; Reflective Judgment; Schematism; Harmonious Free Play